Drugs Abuse and Addiction Behavior in Music as a Threat to Mass Culture: Analytical Study - Zeghdani, Maroua (جامعة العربي التبسي تبسة - مخبر الدراسات الإنسانية والأدبية, 2021)
This paper focuses on music and exactly the American one in its presentation of drug abuse and addiction behavior, the study aimed to understand and clarify values, messages and thoughts sent by these songs to the audience, which are represented in linguistic and visual symbols. Based on this, the study tries to figure out how the American music encourages drugs abuse and addiction, and how it affects the receiver’s mental image about drugs, tobacco, alcohol and its potential threat. By using Frankfurt School as an approach of explanation, discourse analysis as a method, scientific observation as a tool. The research used a purposive sample, composed of six songs in English from different styles of music (hip-hop, rap and Rock). The study found that the American music is glorifying drug addiction and make it socially acceptable for the audience, in order to show it as a lifestyle, which may pose a real threat to social and individual values.
Keywords: تعاطي المخدرات -- الثقافة الجماهيرية -- الموسيقى الأمريكية -- القيم الاجتماعية